Perlindungan Hukum Bagi Hak-Hak Keperdataan Anak Luar Kawin - Abnan Pancasilawati (FENOMENA, 2014)
This study is directed to describe: 1) the guarantee of protection in the law for children rights who are born without marital status, 2) the support of the legal culture of society in the realization of the protection of children rights who are born without marital status. The result of study shows that: (1) The law has not given any guarantee of protection for children rights who are born without marital status. It is because there is no harmonization of the law and it is against the internal law culture where the law enforcers have not run the legal law optimally to conduct a good protection since they should accept or refuse the content of Constitutional Court No. 46/PUU-VIII/2010. (2) The supports of the legal culture of society, in the realization of the protection of children rights who are born without marital status, are good enough as long as they are supporting religious values and justice values which are being applied in the society.